A recalcitrant acrodermatitis continua of Hallopeau successfully treated with etanercept - Narumol Silpa-Archa (2018)
Acrodermatitis continua of Hallopeau (ACH) is considered as a localized form of pustular psoriasis that is usually refractory to the treatment. The condition is characterized by sterile pustules, onychodystrophy, anonychia, and osteolysis of distal phalanges. The authors report a case of recalcitrant ACH who previously failed to topical corticosteroid, methotrexate, acitretin, and phototherapy and rapidly responded to etanercept in combination with acitretin. The primary varicella infection occurred during the therapy. The patient was able to discontinue etanercept within four months after starting the treatment. The lesion was then under-controlled by acitretin and topical clobetasol ointment with an 8-month clinical remission.